THE ROLE OF PARENTS IN CONSPICUOUS CONSUMPTION OF PRESCHOOL CHILDREN - Molchanova, G.V. (Modern Psychology, 2020)
Conspicuous consumption in childhood has distinctive features. It performs compensatory functions. Disharmonious parenting style of education provokes difficulties in communication in children. Children have not the necessary communicative skills to communicate adequately with their peers. They use conspicuous consumption as base of interaction.
Keywords: conspicuous consumption, preschool children, disharmonious parenting style of education.